(0;2]U[4;6)
Пошаговое объяснение:
ОДЗ:
{x > 0;
{6–x > 0 ⇒ x < 6
{(x4–12x3+36x2) > 0⇒ (x·(6–x))2 > 0 ⇒ x≠0; x≠6
ОДЗ: х∈(0;6)
при х∈(0;6):
log2(x4–12x3+36x2)=log2x2·(6–x)2=
log2(x·(6–x))2=2log2x·(6–x)=2log2x+2log2(6–x)
Неравенство принимает вид:
(2–log2x)·(log2(6–x)–2) ≥ 0
Применяем обобщенный метод интервалов
log2x=2 или log2(6–x)=2
x=4 или 6–х=4;х=2
При х=1
(2–log21)·(log2(6–1)–2)=2·(log25–log24) > 0
При х=3
(2–log23)·(log2(6–3)–2)=–(2–log23)2 < 0
При х=5
(2–log25)·(log2(6–5)–2)=(log24–log25)·(0–2) > 0
(0)__+__ [2]__–__[4]__+__ (6)
3/8 * 5 + 5/56 - 1/7 : 1/5 = 1,25
1) 3/8 * 5 = 15/8
2) 1/7 : 1/5 = 1/7 * 5/1 = 5/7
3) 15/8 + 5/56 = 105/56 + 5/56 = 110/56
4) 110/56 - 5/7 = 110/56 - 40/56 = 70/56 = 1 14/56 = 1 1/4 = 1,25
ответ: 1,25